Intron Retention and TE Exonization Events in ZRANB2. (17th June 2012) - Park, Sang-Je; Huh, Jae-Won; Kim, Young-Hyun; Kim, Heui-Soo; Chang, Kyu-Tae
Abstract : The Zinc finger, RAN-binding domain-containing protein 2 ( ZRANB2 ), contains arginine/serine-rich (RS) domains that mediate its function in the regulation of alternative splicing. The ZRANB2 gene contains 2 LINE elements (L3b, Plat_L3) between the 9th and 10th exons. We identified the exonization event of a LINE element (Plat_L3). Using genomic PCR, RT-PCR amplification, and sequencing of primate DNA and RNA samples, we analyzed the evolutionary features of ZRANB2 transcripts. The results indicated that 2 of the LINE elements were integrated in human and all of the tested primate samples (hominoids: 3 species; Old World monkey: 8 species; New World monkey: 6 species; prosimian: 1 species). Human, rhesus monkey, crab-eating monkey, African-green monkey, and marmoset harbor the exon derived from LINE element (Plat_L3). RT-PCR amplification revealed the long transcripts and their differential expression patterns. Intriguingly, these long transcripts were abundantly expressed in Old World monkey lineages (rhesus, crab-eating, and African-green monkeys) and were expressed via intron retention (IR). Thus, the ZRANB2 gene produces 3 transcript variants in which the Cterminus varies by transposable elements (TEs) exonization and IR mechanisms. Therefore, ZRANB2 is valuable for investigating the evolutionary mechanisms of TE exonization and IR during primate evolution.